Proximate Composition and Mineral Content of Selected Edible Mushroom Varieties of Bangladesh (Bangladesh Journal of Nutrition, 2012)
Proximate  composition  and  mineral content of  five species of edible mushrooms namely Pleurotus ostreatus, Pleurotus sajor-caju, Pleurotus florida and Pleurotus HK- 51 belonging to the family: Pleurotaceae and genus: Pleurotus and  Calocybe indica belonging to the family: Tricholomataceae and Genus: Calocybe have been analyzed.Crude protein, total lipids, available carbohydrates, dietary fiber and total carbohydrates  content  in mushrooms  were found to be in the ranges of 3.22-4.83, 0.41-1.05, 4.2-6.37, 0.58-1.11 and 4.82-7.48 g per 100g of fresh edible portion(EP) respectively.  Moisture, total solids and ash content  were found to be in the ranges of 85.95-90.07, 9.93-14.05 and 0.98-2.3 g/100g of fresh EP respectively. Where as total  calorie values in mushrooms  were found to be in the ranges of  35.51 - 50.03 Kcal / 100g  fresh  EP. The values of  Zinc, copper,  iron,  sodium  and  potassium content in mushrooms were found to be in the ranges of 0.65-1.24, 0.14-0.91, 0.94- 1.81, 3.18-37.23 and 19.83-197.24 mg/100g of fresh EP respectively while calcium, magnesium,  phosphorus  and  manganese content were  in the ranges of  0.12-0.58, 27.26-51.21, 22.2-62.1 and  0.17-0.53 mg/100g of fresh EP respectively. DOI: http://dx.doi.org/10.3329/bjnut.v22i0.12832 Bangladesh Journal of Nutrition Vol.22-23 2009-2010 pp.61-68